Perubahan Strategi Pemasaran Perguruan Tinggi Swasta (Studi kebijakan di Universitas Prof Dr. Hazairin Bengkulu) - Anwar, Syaiful (Jurnal Aplikasi Manajemen, 2016)
The purpose of this research is to study the capacity of Prof. Dr. Hazairin Universityin improving health of the organization and changes of marketing strategic. The data consist of the policy effective in Prof. Dr. Hazairin University from 2010 to 2015. Analysis tool used is the SWOT analysis by calculating the strengths, weaknesses, opportunities and threats.This study showed the functioning of market segmentation strategy, targeting strategy, positioning strategy, differentiation, focus and efficiency as element the competitive power of Prof. Dr. Hazairin University. This confirms the importance of applying a total quality management system for enhanced health of the organization a higher educational institution. Â